A study on Entrepreneurship and Innovation in context of economic growth - Aakash Choudhary (AG Volumes, 2022)
Entrepreneurship is probably one of the most influential methods that economic development can be supported, which is among the many various ways that economic development can be pushed. The proliferation of entrepreneurial endeavours around the globe is directly contributing to the expansion of an increasing number of nations. We recognise that if you are a company owner or an entrepreneur who is just beginning to get a grasp on the idea of entrepreneurship, you may feel as like you are about to embark on a monumental adventure, and we empathise with you. You put in a lot of effort, and it could give the impression that your task is more difficult than it really is. The ability to expand one’s company into something more substantial and generate a profit for oneself are not the only goals that should motivate entrepreneurs; they should also be aware that their work has broader implications. All of this individual and professional development has an extremely beneficial effect on the community. Indeed, entrepreneurial activity is the single most important driving force behind an increase in a community’s standard of living and overall economic growth. In order for there to be economic growth, there must be gains in per capita income that are both sustainable and shared, as well as shifts in the structural makeup of an economy toward commodities with greater value added and production processes that are more efficient. By assisting the reallocation of resources from less productive uses to more productive uses, by fulfilling activities within the economy such as “cost-discovery,” “gap-filling,” and “input-completing,” entrepreneurs may make a contribution to the growth and development of the economy.